Significance of elevated MB isoenzyme with normal creatine kinase in acute myocardial infarction. - Yusuf, S; Collins, R; Lin, L; Sterry, H; Pearson, M; Sleight, P (1987)
The significance of elevated levels of the MB isomer of creatine kinase (CK-MB) when creatine kinase (CK) level is normal was studied in 400 patients with suspected acute myocardial infarction (AMI). In 350 patients both CK and CK-MB were elevated (group 1), in 21 only CK-MB was elevated (group 2), in 24 neither enzyme was elevated (group 3) and in 5 only CK was elevated (group 4). In 57% of patients in group 2 the CK level was doubled, with a characteristic enzyme curve, within the normal range, suggesting that an increase in CK had been missed because arbitrary definitions of "normal" were used. The median CK increase (60 IU/liter) in group 2 was greater than that in group 3 (23 IU/liter) (p less than 0.001). Patients in group 1 with small AMIs had a relative increase in CK similar to that in group 2. However, patients in group 2 had a lower baseline CK level so that peak CK did not become abnormally high despite a 5-fold increase in some patients. In patients in group 1 with small AMIs, CK was elevated in fewer samples than CK-MB. If only 2 samples were obtained in all patients, elevation of CK levels would have been missed in 63 group 1 patients, erroneously increasing the number of patients in group 2 fourfold (to 84 of 400, or 21%, instead of 21 of 400, or only 5%). Conversely, if patients in group 2 with a doubling of CK are excluded, the prevalence of elevated CK-MB with normal CK would be only 9 of 400 (2%).(ABSTRACT TRUNCATED AT 250 WORDS)